Analisis Aspek Substansif dan Prosedural pada Sengketa Wanprestasi Pembiayaan Akad Murabahah: (Studi Kasus Putusan Pengadilan Agama) (Lembaga Pengembangan Kinerja Dosen, 2025)
The development of Islamic banking in Indonesia has introduced the murabahah contract as one of the most dominant financing products. However, in practice, this contract often gives rise to legal disputes, particularly due to default by customers who fail to fulfill their payment obligations in accordance with the agreement. This study focuses on the Palangka Raya Religious Court Decision Number 1/Pdt.GS/2024/PA.PLK, which is noteworthy because, although the substance of the claim has a strong legal basis, it was deemed inadmissible due to a formal defect in the special power of attorney. The aim of this research is to analyze how substantive aspects related to default in murabahah contracts and procedural aspects concerning the mechanism of simplified lawsuits, as well as the validity of a special power of attorney, can affect dispute resolution.This article employs a qualitative method with a normative juridical approach, encompassing legislation, conceptual analysis, and case studies. Primary data were obtained from court decisions, while secondary data were drawn from legal regulations and literature studies. The study shows that substantively, the defendant was proven to be in default for failing to fulfill payment obligations under the murabahah contract, giving the plaintiff a strong legal basis to file a claim. However, procedurally, the lawsuit was inadmissible because the submitted special power of attorney did not meet formal requirements, rendering the plaintiff’s legal representative unauthorized to act on their behalf. The implications of these findings indicate that the success of resolving Islamic banking disputes is not solely determined by the strength of the claim’s substance, but also heavily depends on compliance with the applicable civil procedural laws. Therefore, fulfilling procedural requirements is a crucial factor in ensuring the effectiveness of dispute resolution in Islamic banking.